2021
DOI: 10.3390/ijerph18094473
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practice of Indonesian Residents toward COVID-19: A Cross-Sectional Survey

Abstract: Coronavirus disease 2019 (COVID-19) has become a pandemic. We examined the KAP’s relationship with factors associated with practice toward the COVID-19 pandemic in Indonesia. This cross-sectional survey study was conducted between March and April 2020 and included 1033 participants. Knowledge scores of COVID-19 were positively associated with wearing a mask when leaving home (odds ratio (OR): 1.22, p < 0.05). Although men had a lower knowledge score, they were less likely to go to a crowded place compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 49 publications
(76 reference statements)
3
24
2
Order By: Relevance
“…These discrepancies could be attributed to a lack of capability of older adults to implement good preventive practices in rural and resource-limited settings such as in Malang. Older population characteristics in previous KAP research in Malaysia, Saudi Arabia, Palestine, and Bangladesh were largely from a high school education or higher level [ 24 , 38 , 39 , 42 , 44 ], whereas older population characteristics in this current study were mostly from an elementary education or lower level. In addition, most older adults in Malang often do not have access to health facilities and sources [ 45 ], while prior KAP research in Malaysia, Saudi Arabia, Palestine, and Bangladesh focused on urban settings, where senior persons often have easier access to health facilities and resources.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…These discrepancies could be attributed to a lack of capability of older adults to implement good preventive practices in rural and resource-limited settings such as in Malang. Older population characteristics in previous KAP research in Malaysia, Saudi Arabia, Palestine, and Bangladesh were largely from a high school education or higher level [ 24 , 38 , 39 , 42 , 44 ], whereas older population characteristics in this current study were mostly from an elementary education or lower level. In addition, most older adults in Malang often do not have access to health facilities and sources [ 45 ], while prior KAP research in Malaysia, Saudi Arabia, Palestine, and Bangladesh focused on urban settings, where senior persons often have easier access to health facilities and resources.…”
Section: Discussioncontrasting
confidence: 50%
“…Earlier studies in Malaysia, Saudi Arabia, Palestine, and Indonesia have also shown that senior adults are more likely to have more accurate KAP regarding COVID-19 prevention than young adults [ 24 , 38 , 39 , 42 ]. As senior adults have more health concerns and needs, they are more likely to seek and find accurate health information than young adults [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Study also highlighted that person aged 45+ years, female, urban residents, Indian ethnicity, non-Malaysian, higher education, ever married and good income were more likely to have good practice and all are significant to COVID-19 prevention practices in Malaysia. By systematic review, we also observed age, gender, region and occupation as the significant factor of persons' practice toward COVID-19 (1,23,29,33,(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)65). Hence, these findings suggest that health education interventions targeting particular groups such as younger people, men, lower educated persons, people with a less monthly income and rural residents should be designed in order to improve COVID-19 awareness, which can play vital role in improving the practice of individual's preventive attitudes (1,64).…”
Section: Discussionmentioning
confidence: 82%
“…In response to COVID-19, different countries in Southeast and South Asia were also raised an alert and implemented wide-ranging, multi-agency public health measures under WHO guidelines to fight against the pandemic. As COVID-19 appears to be transmitted from person to person, almost all countries in Southeast and South Asia initiated a public campaign highlighting the necessity of practicing respiratory hygiene, hand hygiene and using appropriate personal protective equipment (PPE) ( 1 , 23 , 28 , 29 , 43 , 44 , 47 , 49 , 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, human behaviors were tremendously linked to the COVID-19 pandemic, where the control measure of close contact could reduce the infection risk of its virus up to 47% [19]. A study conducted by Muslih et al [20] shows that study respondents had a good knowledge, positive attitude, and were conducting appropriate practices in preventing the spread of COVID-19. However, this previous study only assessed the practice of avoiding crowded places and masks used, and it did not measure other behavior such as touching surfaces, parts of bodies, the use of disinfectant, hand-washing, etc.…”
Section: Introductionmentioning
confidence: 99%